Comparing critical success factors between European M&As in China and Chinese M&As in Europe: A mixed-method analysis. Issue 7 (14th November 2016) - Chen, Yu; Werle, Herbert; Moser, Roger
Abstract : Purpose: The purpose of this paper is to compare the critical success factors (CSFs) between two groups of European mergers and acquisitions (M&As) in China and Chinese M&As in Europe. Design/methodology/approach: In the paper, a mixed-method research design which combines primary case study with secondary questionnaire survey is applied. Findings: The findings from the case study show the main differences with respect to CSFs between the two groups are related to: importance of relationship building in Chinese culture, Chinese culture trait of high power distance, Chinese decision process, complicated Chinese approval process for foreign companies doing M&As in China, integration of acquired Chinese/European company, and relatively new phenomenon of Chinese acquisitions in Europe. The Mann-Whitney-Wilcoxon test from the questionnaire survey provides statistical support for significant difference between the two groups regarding the factor of involvement and commitment of acquiring companies' entrepreneurial CEO/chairman in the M&A process. Originality/value: This paper is among the first attempts to conduct a comparative study which provides new insights into the differences between the CSFs in European M&As in China and in Chinese M&As in Europe.